(untitled) (Konturen, 2026)
This essay examines Kafka’s chronic struggle with writer’s block from the perspective of disciplinary violence, and uses it to expand on Dungey’s thesis, that Kafka saw writing as a means of creating an artistic subjectivity. By studying Kafka’s letters and diaries it becomes clear that Kafka saw writing as in inherently violent act that was capable of maintaining a dialectical tension between his ‘real’ and ‘artistic’ selves, and this raises the question of whether his suffering was warranted. Through a reading of In the Penal Colony, we can see how Kafka explored this dilemma in his own writing, and how it resulted in a loss of authorial control over the symbolic nature of the text.